Innovative Technology for Production of Electrical Cabinets Using Laminated Conductors - Marija Odak; Josipa Stegic; Igor Erceg; Damir Sumina; Elvedin Topcagic (IEEE Access, 2023)
Electrical cabinets are assembled manually to a great extent. The existing wiring technology of electrical cabinets is a big consumer of plastic materials used for the wire ducts which make up a large portion of the cabinet volume. Also, the current electrical cabinet production requires a lot of human labor. This paper proposes a new laminated conductor technology used for connecting electrical cabinet components. The approach is based on alternately stacking conductive and insulating layers. The primary advantage of the new technology is the possibility of accomplishing a fully automated production by using laminated conductors of rectangular cross sections for interconnecting the components. Additional benefits are reduced size, approximately by 70%; and a simplified use and installation. Both thermal and mechanical simulation analyses were carried out in the study. The final product of this technological development and its application is a prototype, which was evaluated experimentally for its electrical and mechanical functionality. Thermal conditions were also tested. The tests that were performed in this study include also mechanical testing on the bolts in the circuit block and electrical current tests. The experimental results justify the application of the proposed technology.